2020
DOI: 10.1504/aajfa.2020.104406
|View full text |Cite
|
Sign up to set email alerts
|

The determinant of capital adequacy ratio: empirical evidence from Vietnamese banks (a panel data analysis)

Abstract: The purpose of this study is to investigate the determinant of Vietnamese banks' capital adequacy ratio (CAR) by internal banking factors. Secondary data is collected from banks' annual reports in the period of 2009-2015. FGLS method and panel data are used to examine a regression model with CAR is the dependent variable and five independent variables: bank size (SIZE), loans (LOA), loan loss reserve (LLR), liquidity (LIQ), profitability (ROE). The results show that SIZE and LIQ impact negatively on CAR with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…Ozili (2015) conducted an empirical study and discovered that bank profitability is significantly influenced by bank capital adequacy, which is a crucial determinant of bank profitability. Thoa et al (2020) investigated the determinants of Vietnamese banks' CAR using secondary data from banks' annual reports during 2009-2015. The study used panel data and found that bank size and liquidity had a significant negative impact on CAR, while loan loss reserve and loans had a negative impact but were statistically insignificant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ozili (2015) conducted an empirical study and discovered that bank profitability is significantly influenced by bank capital adequacy, which is a crucial determinant of bank profitability. Thoa et al (2020) investigated the determinants of Vietnamese banks' CAR using secondary data from banks' annual reports during 2009-2015. The study used panel data and found that bank size and liquidity had a significant negative impact on CAR, while loan loss reserve and loans had a negative impact but were statistically insignificant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bank capital as measured by the capital adequacy ratio (CAR) is determined to be a minimum of 8% of risk-weighted assets (Bank Indonesia, 2011). If the capital is large enough, it can also be used to increase the credit distributed, thereby increasing profitability (Thoa, Anh, & Minh, 2020). Siddique et al, (2022); Ikpesu & Oke., (2022) and Mir & Shah., (2022) found that CAR had a positive effect on profitability, while Sari et al, (2022) and (Sahyouni & Wang, 2019) actually found that CAR had no effect on profitability.…”
Section: Ijfbs Vol 12 No 3 Issn: 2147-4486mentioning
confidence: 99%
“…Pertumbuhan kredit (loan) yang tinggi berpengaruh secara signifikan terhadap variabel tertentu dari bank. Pertumbuhan kredit antar tahun meningkatkan nonperforming loans (NPL) yang pada akhirnya dapat menurunkan tingkat Capital adequacy ratio (CAR) bank dengan jeda waktu beberapa tahun karena bank harus menanggung kerugian kredit (loan loss) dari NPL tersebut (Amador, Gómez-González, dan Pabón, 2013;Kashif, Iftikhar, dan Iftikhar, 2016) dan cadangan kerugian kredit (loan loss reserves) meningkat akibatnya berpengaruh negatif terhadap rasio kecukupan modal (CAR) bank (Blose, 2001;Dreca, 2013;Thoa, Anh, dan Minh, 2020).…”
Section: Kajian Literatur Dan Pengembangan Hipotesisunclassified
“…Bukti ini mendukung hasil penelitian Amador, Gómez-González, dan Pabón, (2013); Kashif, Iftikhar, dan Iftikhar, (2016). Selain itu cadangan kerugian kredit (loan loss reserves) yang harus disediakan oleh bank juga tetap tinggi sehingga berpengaruh negatif terhadap rasio kecukupan modal (CAR) bank (Blose, 2001;Dreca, 2013;Thoa, Anh, dan Minh, 2020). Distribusi kredit (loan) yang tinggi tersebut mereduksi nilai rasio modal karena jumlah kredit yang tinggi memperbesar provisi kerugian kredit yang akhirnya menggerus nilai modal (Baradwaj et al, 2015;Foos et al, 2010;Messai dan Jouini, 2013).…”
Section: Metode Penelitianunclassified